ANALISIS KELAYAKAN BUTIR SOAL KESEHATAN DAN KESELAMATAN KERJA MENGGUNAKAN SOFTWARE ANATES - Nadhirra Shaffa Aprillia Faatiha; Nayla Aurelia Putri; Nafaza Zakiyah Qolbi Agustin; Friska Putri Amelia; Dian Merta Halatu; Luqman Hakim; Vivi Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the quality of multiple-choice test items in the Occupational Safety and Health (K3) Teaching Module using a quantitative descriptive approach. A total of 45 items were administered to 25 respondents, consisting of vocational high school students and accounting students, through Google Forms. The Anates software was used to examine item validity, reliability, difficulty level, discrimination index, and distractor effectiveness. The results show that the test has a very high reliability coefficient of 0.96, indicating excellent internal consistency. The validity analysis reveals that 33.33% of the items fall into the very high category, 17.78% high, 15.56% moderate, 6.67% low, and 26.67% very low. In terms of difficulty, most items are categorized as easy to moderate, while several are very difficult, suggesting an imbalanced distribution. Analysis of the discrimination index indicates that most items effectively distinguish between high- and low-performing students, although some items require revision due to low or negative discrimination values. The distractor analysis also shows variation in effectiveness, with some options failing to function as intended. Overall, the test is considered reliable and generally representative, but revisions to items with low validity, extreme difficulty levels, weak discrimination power, and ineffective distractors are recommended to enhance the overall quality of the assessment instrument.